Successful Digital Marketing Techniques for Business Development - Sausan Raihana Putri Junaedi; Victoriani; David Edmond (Pandawan Sejahtera Indonesia, 2024)
In the constantly changing digital environment, digital marketing has emerged as a crucial component of company growth. Effective digital marketing techniques are thoroughly discussed in this article as the key to achieving significant business growth. This article's major goal is to give readers a thorough grasp of the value of identifying the target audience, creating high-quality content, optimizing it for search engines, using social media, using data analysis, and being responsive to shifting digital trends. We also go over the advantages of using this method, including how it can improve visibility, customer retention, and business conversions. This article seeks to serve as a comprehensive how-to manual for businesses and entrepreneurs who wish to learn the art of digital marketing for long-term company expansion.